Characteristics of the representative performance of the mother figure in the Iraqi Child Theater shows - Diwan, Salman Mazhar (Al-Adab Journal, 2021)
This research (Characteristics of the representative performance of the mother’s character in the Iraqi Child Theater) came to identify the mechanisms of the actor’s work in embodying the mother’s character in the child’s theater and to access the performance characteristics.The research included four chapters: the first of which is the methodological framework for the research included the research problem and the need for it based on the following question: How to identify the characteristics of the mother’s character’s performance in the child's theater, what are the ways to perform it and how to present it by the Iraqi theater actor, then the importance of the research, its goal and its limits and define terminology.As for the second chapter (the theoretical framework), it has been divided into two topics: The first topic: the researcher divided it into:The mother's personality and its psychological and social aspects.The mother's personality and her educational role in the theater.The second topic: Characteristics of representational performance in child’s theater, in which the main performance methods in child’s theater and the techniques (sound and physical) used in the performance were addressed.As for the third chapter (Research Procedures), it included the research community, the method of research, and the determination of the sample that the researcher decided to be intentional and selective, then the research tool, and finally the sample that focused on the representative performance of the mother’s character in the child's theater was analyzed in the theatrical performance (the gentle dove).The fourth chapter includes a discussion of the findings and conclusions related to the goal, recommendations and proposals, followed by a list of sources and references, and then the annexes.